Hubungan Tingkat Stres dengan Kepatuhan Minum Obat Pasien Hipertensi di Puskesmas Kediri III - Oktaviani, Ni Putu Ratih; Putu Thrisna Dewi, Ni Luh; Pamungkas , M. Adreng (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Hypertension is a chronic health condition that requires long-term treatment and consistent medication adherence. Psychological factors, particularly stress, play a significant role in influencing patients ability to adhere to antihypertensive therapy. High stress levels may disrupt concentration, reduce motivation, and contribute to forgetfulness, ultimately lowering adherence. This study aimed to determine the relationship between stress levels and medication adherence among hypertensive patients at UPTD Puskesmas Kediri III. This study employed an quantitative correlational design with a cross-sectional approach. A total of 100 hypertensive patients were selected as respondents. The Perceived Stress Scale (PSS-10) was used to assess stress levels, while the Morisky Medication Adherence Scale (MMAS-8) measured medication adherence. The results showed that most respondents experienced mild stress (45.0%), followed by moderate (44.0%), and severe stress (11.0%). Medication adherence was predominantly in the moderate category (59.0%). Statistical analysis using the Spearman Rank test indicated a significant relationship between stress levels and medication adherence (p < 0.05) meaning that stress levels are have correlation with patient consistency in following therapy increasing stress may reduce adherence. These findings highlight the importance of stress management and continuous health education to improve medication adherence among hypertensive patients, thereby supporting better blood pressure control and reducing potential complications